The effect of product quality, brand image, promotion, and price on consumer purchase decisions in umkm on car-free day kab. Jember - Angga Ade Permana; Dedy Wijaya Kusuma; Wasana Sinrungtam; Ihrom Caesar Ananta Putra; Abdul Wahid (LPPM Institut Teknologi dan Sains Mandala, 2025)
Previous research is the most important thing in a research or scientific article. Previous research is useful for strengthening theories and phenomena that affect variables. This article reviews the Influence of Product Quality, Brand Image, Promotion and Price on Consumer Purchasing Decisions at UMKM Car Free Day Kab. Jember. The purpose of writing this marketing management literature review article is to build a hypothesis that can be used in further research. The results of this study are: 1) Product Quality partially does not affect consumer Purchasing Decisions; 2) Brand Image partially does not affect consumer Purchasing Decisions; 3) Promotion partially affects consumer Purchasing Decisions; 4) Price partially does not affect Consumer Purchasing Decisions; 5) Product Quality, Brand Image, Promotion and Price simultaneously affect Consumer Purchasing Decisions at UMKM Car Free Day, Jember regency.